The ecopolitics of consumption : the food trade - Davis, H. Louise, 1974-; Pilgrim, Karyn, 1968-; Sinha, Madhudaya, 1968- (Ecocritical theory and practice., 2016)
This collection adds a new dimension to the field of ecocritical theory by merging multidisciplinary approaches to food studies with the established ecocritical discourse of culture and the environment. Encompassing a theme of confinement and control through the global industrial food systems, the collection explores the role of consumption and commodification in contemporary life and points to new directions for resistance and change.